MODEL MATEMATIKA UNTUK MENDETEKSI DIABETES MELLITUS TIPE - Debora C Sihombing; Kartono Kartono (Jurnal Matematika, 2014)
Diabetes Mellitusis a disease causedby a deficiency ofthe insulin hormone,, resulted concentrationina person's bloodsugaris highbecausesugarin the bloodcan not be usedby the body. Detection ofdiabetesmellituscan be constructedin the form ofmathematicalmodelstoform adifferentialequation. The equations ofthe differential model is asystem ofnonlineardifferentialequationswithtwovariables. The modeltakesthe form ofsystematicnonlinearlinearization. LinearizationperformedbyTaylor seriesapproach. Toillustratethe modelsimulationby givingthe values ofthe calibrationparameters areprocessedby thesolvertools and obtainedtoindicatethe patient'snaturalperiodwithin thenormalglucoseislessthan4hours.Keywords: diabetesmellitus, oscillations, solvertools, linearsystem.